20th century Britain : economic, cultural and social change - Robertson, Nicole; Singleton, John, 1960-; Taylor, Avram, 1962- (Abingdon, Oxon : New York, NY : Routledge, 2023)
"20th Century Britain provides an authoritative and accessible survey of contemporary research on economic activity, society, political development and culture. Written by leading academics, it examines recent advances in scholarship and gives a grounding in established approaches and topics. This collection provides an essential guide to current academic thinking on the most important elements of twentieth-century British history and is a useful tool for all students and scholars interested in modern Britain"--
Introduction: Twentieth-Century Britain / Nicole Robertson, John Singleton and Avram Taylor -- Part A: Britain since -- The British Political System / Richard Toye -- The British Economy / John Singleton -- Inequality, Living Standards, and Welfare Provision / Peter Scott and James T. Walker -- Britain's Changing Position in the International Economy / Catherine R. Schenk -- Managing the Economy, Managing the People / Jim Tomlinson -- Work, the Labour Market and Trade Unions / Chris Wrigley -- Leisure, Consumption and Consumerism / Peter Scott -- The Environment and Environmental Policy / Martin Chick -- Big Business and Management in Britain / John F. Wilson -- Empire and Decolonisation / Paul Ward -- Ethnicity, Identity and Multiculturalism / Sarah Hackett -- Women and Inequalities / Pat Thane -- Disability and Disabled People / Vicky Long -- Social Mobility / Andrew Miles -- Gender and Sexuality / Stephen Brooke -- Healthcare, Health and Wellbeing / Victoria Bates -- Part B: Britain in Focus -- Britain at War 1914-1918 and 1939-45 / Linsey Robb -- The Impact of the Interwar Depression on the Working Class / Stephanie Ward -- Civil Society, Voluntary Action and Citizenship, c. 1918 -1960s / Helen McCarthy -- Heterosexual Sexuality in Britain, 1918-1972 / Hannah Charnock and Kate Fisher -- Britain and Europe since 1945 / Neil Rollings -- The 1960s and the Cultural Revolution / Marcus Collins -- Resisting Racism in 1970s and 1980s Britain: the Experience of Young South Asians / Anandi Ramamurthy.
Keywords: Great Britain -- History -- 20th century; HISTORY / Modern / 20th Century; HISTORY / Europe / Great Britain